Gut microbiome with RAS mutation and chemotherapy response in patients with advanced or metastatic colorectal cancer: a pilot, exploratory study - Kim, Jwa Hoon; Kim, Boyeon; Lee, Jiwon; Kim, Jin; Kwak, Jung-Myun; Lee, Soohyeon (Frontiers in Oncology, 2025)
The gut microbiome plays a pivotal role in tumor–microenvironment interactions, inflammation modulation, and immune regulation, thereby affecting the response to anticancer therapy. This pilot study investigated gut composition according to clinical characteristics and its association with chemotherapy response in patients with metastatic colorectal cancer (mCRC). Seventeen patients were treated with first-line chemotherapy at Korea University Anam Hospital between 2021 and 2023. Stool samples were collected from 15 patients at baseline, during chemotherapy, or at the time of disease progression, and 16S rRNA sequencing was performed. As a result, among lifestyle factors affecting the development of CRC, smoking habits showed weak differences in beta diversity. Non-smokers predominantly harbored bacteria such as Butyricicoccaceae, Ruminococcaceae, Faecalibacterium, and Lachnospiraceae_NK4A136_group, whereas Smokers were associated with Actinomyces and Solobacterium. In terms of baseline characteristics and chemotherapy response, beta diversity exhibited notable differences according to RAS mutation status, and LEfSe analysis indicated that Holdemanella, Anaerostipes, and Collinsella were significantly enriched in patients with RAS mutations. Chemotherapy Responders harbored more beneficial bacteria, notably Lactobacillus, despite the lack of differences in diversity between the responder and Non-responder groups. According to disease control during follow-up, Bifidobacterium abundance significantly increased in the non-progressive disease group. This study suggests that gut microbiome composition is associated with smoking history, RAS mutation status, and chemotherapy response in patients with mCRC. These findings highlight the potential role of the gut microbiome as a biomarker to predict treatment response and prognosis, with its composition shaped by both host lifestyle factors and genetic mutations.